Pithovirus sibericum, a new bona fide member of the “Fourth TRUC” club - Sharma, Vikas; Colson, Philippe; Chabrol, Olivier; Pontarotti, Pierre; Raoult, Didier (Frontiers in Microbiology, 2015)
Nucleocytoplasmic large DNA viruses, or representatives of the proposed order Megavirales, include giant viruses of Acanthamoeba that were discovered over the last 12 years and are bona fide microbes. Phylogenies based on a few genes conserved amongst these megaviruses and shared by microbes classified as Eukarya, Bacteria and Archaea, allowed for delineation of a fourth monophylogenetic group or “TRUC” (Things Resisting Uncompleted Classification) composed of the Megavirales representatives. A new Megavirales member named Pithovirus sibericum was isolated from a >30,000-year-old dated Siberian permafrost sample. This virion is as large as recently described pandoraviruses but has a genome that is approximately three to four times shorter. Our objective was to update the classification of P. sibericum as a new member of the “Fourth TRUC” club. Phylogenetic trees were constructed based on four conserved ancient genes and a phyletic analysis was concurrently conducted based on the presence/absence patterns of a set of informational genes from members of Megavirales, Bacteria, Archaea and Eukarya. Phylogenetic analyses based on the four conserved genes revealed that P. sibericum is part of the fourth TRUC composed of Megavirales members, and is closely related to the families Marseilleviridae and Ascoviridae/Iridoviridae. Additionally, hierarchical clustering delineated four branches, and showed that P. sibericum is part of this fourth TRUC. Overall, phylogenetic and phyletic analyses using informational genes clearly indicate that P. sibericum is a new bona fide member of the “Fourth TRUC” club composed of representatives of Megavirales, alongside Bacteria, Archaea and Eukarya.